2002
DOI: 10.1046/j.1463-1326.2002.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Pro12Ala mutation of the PPAR‐gamma receptor gene on metabolic and clinical characteristics in treatment‐naïve patients with type 2 diabetes

Abstract: Peroxisome proliferator activated receptor-gamma is an important factor in adipocyte differentiation and energy metabolism and is thus a candidate gene for obesity, insulin resistance and dyslipidaemia. We therefore assessed the associations between the most common variant of the PPAR-gamma, the Pro12Ala (P12A) substitution in the PPAR-gamma 2 gene, with BMI, blood pressure, fasting plasma glucose, HbA1c, total cholesterol, LDL and HDL cholesterol and plasma triglyceride in 183 treatment-naïve patients with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
(8 reference statements)
1
9
0
Order By: Relevance
“…Potentially, a mechanism including higher leptin levels and leptin resistance may explain higher fat intakes in obese individuals carrying the Ala12 allele. PPAR γ Pro12Ala has been inconsistently associated with BMI [58,67,68]. In the present study, BMI and energy intakes were comparable between genotypes.…”
Section: Discussionsupporting
confidence: 52%
“…Potentially, a mechanism including higher leptin levels and leptin resistance may explain higher fat intakes in obese individuals carrying the Ala12 allele. PPAR γ Pro12Ala has been inconsistently associated with BMI [58,67,68]. In the present study, BMI and energy intakes were comparable between genotypes.…”
Section: Discussionsupporting
confidence: 52%
“…Many molecules are involved in the differentiation of preadipocytes into mature adipocytes. C/EBPα and PPARγ play important roles among these molecules: PPARγ can induce the maturation of adipocytes and regulate the expression of adipogenesis-related genes, whereas C/EBPα can regulate the terminal differentiation of adipocytes (12)(13)(14)(15). Thus, the overdifferentiation of adipocytes and abnormal deposition of adipose tissues might be related to the increased expression of C/EBPα and PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the positive studies summarized above, we identified 40 studies dealing with 27 candidate genes in which there were no associations between DNA sequence variations and obesity‐related phenotypes. Among these studies, the most frequent were those pertaining to markers of UCP2 (142, 143, 144, 145) (four studies), ADRA2B (146, 147, 148), ADRB2 (149, 150, 151), PPARG (86, 152, 153), and RETN (154, 155, 156) (three studies each). Other markers yielding negative findings were those related to ACE (157), ADRB3 (158), APOE (159, 160), CAPN10 (161), CYP27B1 (162), DGAT1 (163), DRD2 (164), EDN1 (165, 166), ESR1 (167), F7 (168), FABP2 (169), GNB3 (170), GPR10 (171), IL6 (172, 173), IRS1 (174), IRS2 (174), LEPR (175), LPL (176), NOS3 (177), NR0B2 (178), SORBS1 (179), and TNF (180).…”
Section: Qtls From Crossbreeding Experimentsmentioning
confidence: 99%